Granulomatosis con poliangitis en pediatría : a propósito de un caso con síndrome pulmón-riñón (2013)
ABSTRACT: Granulomatosis with polyangiitis as a cause of kidney-lung syndrome is uncommon in children. We report the case of a 13 year old patient with alveolar hemorrhage, rapidly progressive glomerulonephritis, episcleritis and anti PR3. We refer to features of the ANCA-associated vasculitis in children and to its therapeutic approach.